Mediated Futures in Anesthetic Space - Piotr M. Szpunar (Media Theory, 2024)
Media are intimately connected to the future. They are simultaneously posited as encouraging speculation and foreclosing futures. Through an examination of the “canal craze” at the turn of the twentieth century in which the telescopic lens was believed to reveal Earth’s future by way of focusing in on its nearby twin, this paper moves beyond notions of open and closed visions by considering the function of noise in mediated futures. That the canals were an effect of dust, as both elemental medium and noise, encourages broader questions concerning how futures pivot on what lies at the blurred edges of media and beyond rather than on what media make clearly visible. This paper argues for an analytic of futures, both potential and prescribed, situated in the anesthetic fields of media ecologies, spaces of speculation, contestation, and the non-dyadic play of visibility-opacity-invisibility.